The Effect of Intralesional Propolis on Transforming Growth Factor-β (TGF-β) Expression in Tendon Healing: An Experimental Study in a Wistar Rat Model of Partial Achilles Tendon Rupture - Luthfi Walikram; Nino Nasution; Andriandi Andriandi (GLOBAL HEALTH SCIENCE GROUP, 2026)
Transforming growth factor-beta (TGF-β) regulates tendon repair, but dysregulated expression contributes to fibrosis. Propolis contains flavonoids and phenolics with immunomodulatory activity and may influence TGF-β signaling. This study evaluated intralesional propolis on TGF-β expression in a Wistar rat partial Achilles rupture model. A true experimental post-test only control group design was used. Male Wistar rats underwent standardized partial Achilles transection (30–40% thickness) and were randomized to: 50% propolis 0.1 mL intralesional (n=9), 0.9% NaCl 0.1 mL (n=9), or no injection (n=9). On day 35, tendons were harvested for immunohistochemistry using an IHC World–based scoring (H-score 0–300) assessed in ≥5 high-power fields by two independent raters. Interobserver agreement was moderate (κ=0.444, p<0.001). TGF-β H-score categories differed significantly among groups (Kruskal–Wallis p<0.001). The propolis group shifted toward higher expression: 88.9% (8/9) were 101–200 and 11.1% (1/9) were 51–100, whereas both comparator groups clustered at 0–50 (44.4%) and 51–100 (55.6%), with none ≥101. Intralesional 50% propolis increased TGF-β immunohistochemical expression at day 35 after partial Achilles rupture, suggesting enhanced regenerative signaling during tendon healing. Further studies should assess dose–response effects and biomechanical outcomes in vivo.